Development of a Student Worksheet (LKPD) Based on Socio-Scientific Inquiry (SSI) to Improve Critical Thinking Skills of Grade XI Students on the Topic of the Reproductive System at SMA Swasta Cerdas Murni - Lendy Fadhillah; Ummi Nur Afinni Dwi Jayanti (Bioedukasi: Jurnal Pendidikan Biologi, 2025)
The research aimed to develop a Socio-Scientific Inquiry (SSI)-based Student Worksheet (LKPD) on the topic of the human reproductive system to improve the critical thinking skills of Grade XI students in senior high schools (SMA/MA). The development process employed the 4D model (Define, Design, Develop, Disseminate) proposed by Thiagarajan. Research instruments included validation sheets, practicality questionnaires, and critical thinking tests, which were analyzed using pretest and posttest data. Validation was carried out by media experts, subject matter experts, and SSI approach experts. Practicality was assessed by both teachers and students, while effectiveness was measured using the N-Gain score. The validation results showed that the developed LKPD was highly valid, with an average percentage score of 91.6%. Practicality testing indicated that the LKPD was highly practical, with teacher responses at 96% and student responses at 92%. The effectiveness of the product was demonstrated by an N-Gain score of 0.84, categorized as high. Therefore, the SSI-based LKPD is proven to be valid, practical, and effective in enhancing students’ critical thinking skills. This product is also relevant to contextual learning in the Merdeka Curriculum and offers an innovative alternative for biology education